(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study assesses the challenges faced by Small and Medium Enterprises (SMEs) in Tanzania in accessing bank loans. Design/Methodology/Approach: The research was conducted in Ilala Municipality, where a structured questionnaire was administered to 80 respondents. The study employed a multistage sampling followed by stratified sampling to categorise respondents based on the banks from which they sought loans: NMB Bank, CRDB Bank, and NBC Bank. Simple random sampling was utilised to sample subjects for the study. Multiple regression models were used to examine the effect of the dependent variables on the response. Findings: Regression analysis revealed that the characteristics of SME owners (marital status, age, education) and bank requirements for loans (interest rates and collateral) significantly affect SMEs’ ability to access loans. These findings imply that the characteristics of SME owners and bank requirements play a crucial role in limiting or enabling access to financial resources for SMEs. Research Limitation: Because of financial constraints and time limitations, the data is limited to a particular area, especially the Ilala district and not the Dar es Salaam region. Hence, the data presented does not represent the issues across the entire Dar es Salaam region. Practical Implication: Based on these findings, the study recommends that banks consider revising their loan requirements. Social Implication: SME owners must enhance their financial literacy, including keeping a good record of business returns, to improve their chances of securing funding. Originality/value: The regression approach offers a more robust statistical foundation for understanding SME financing constraints than the descriptive or qualitative methods that dominate existing literature in this field.